The Human Rights Protection in The Process of Justice - Charolina (Yayasan Cinta Negara, 2025)
Legal regulations on the protection of human rights can be guided by Law No. 39/1999, but in the process of enforcing the law in court, legal protection is only limited in an abstract form, namely against the perpetrators of the crime, while for the victim it has not been regulated concretely by law, so that the rights of the victim are always put aside and this according to the law clearly violates human rights. The protection of human rights in the judicial process should be concrete and not abstract, therefore in an effort to protect human rights in law enforcement in order to achieve real or substantive justice the decision must consider the interests of the victim, even though the law has not been expressly regulated, but judges as law creators and law inventors must have the courage to make new laws so that the perpetrator is not only punished by the body, but must be responsible for the losses suffered by the victim. In the judicial process, the judge can apply this responsibility in 2 (two) ways, namely: Civil Liability and Criminal Liability, so that the legal protection of victims in the judicial process is truly felt to be fair by both parties, so that the victim as the aggrieved party or the complainant in a case that he has suffered